Professionalism among public and nonprofit managers: a comparison - Berman, Evan M. (1999)
In recent years, considerable attention has focused on professional orientations of managers in public and nonprofit organizations, especially with regard to ethics. This article reports on a comparative survey among top managers in local government, social service organizations, and museums. Knowledge of comparative, professional orientations is also relevant to many public administration programs that increasingly offer nonprofit management "tracks" or electives to students. This study finds that whereas levels of professionalism among public and nonprofit managers are similar, public and nonprofit organizations experience different conditions that affect it. This article also reports on the use of management of change strategies in public and nonprofit organizations. On balance, many similarities are found between public and nonprofit organizations. - Reproduced
Keywords: Managers